2022
DOI: 10.1038/s42003-022-03339-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention improves health metrics and life expectancy of the genetically obese Titan mouse

Abstract: Suitable animal models are essential for translational research, especially in the case of complex, multifactorial conditions, such as obesity. The non-inbred mouse (Mus musculus) line Titan, also known as DU6, is one of the world’s longest selection experiments for high body mass and was previously described as a model for metabolic healthy (benign) obesity. The present study further characterizes the geno- and phenotypes of this non-inbred mouse line and tests its suitability as an interventional obesity mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 106 publications
(142 reference statements)
1
6
0
Order By: Relevance
“…Late dietary restriction in these mice demonstrated antiobesity effects including decrease in fat content and improvement of expression of genes involved in lipid synthesis. This supports the use of "Titan" mice as a model of metabolic disorders, systemic inflammation, and early aging [55].…”
Section: Drosophila Melanogastersupporting
confidence: 63%
See 1 more Smart Citation
“…Late dietary restriction in these mice demonstrated antiobesity effects including decrease in fat content and improvement of expression of genes involved in lipid synthesis. This supports the use of "Titan" mice as a model of metabolic disorders, systemic inflammation, and early aging [55].…”
Section: Drosophila Melanogastersupporting
confidence: 63%
“…Genetic Models. Metabolic syndrome negatively affects healthy longevity but takes years to study in mammalian models, thereby delaying the development of translational applications [55]. Therefore, development of genetic mammalian models with shortened lifespan and fast progression to an obese phenotype has become a convenient approach to use for obesity studies.…”
Section: Drosophila Melanogastermentioning
confidence: 99%
“…The median and maximum lifespan of Titan mice are 46 and 88 weeks respectively. We have also shown that the mice are responsive to dietary intervention, resulting in improved health metrics and extended lifespan 3 .…”
Section: Main Partmentioning
confidence: 77%
“…The median and maximum lifespan of Titan mice are 46 and 88 weeks respectively. We have also shown that the mice are responsive to dietary intervention, resulting in improved health metrics and extended lifespan 3 . However, the question of whether these mice could be used to study aging and longevity interventions remained underexplored.…”
Section: Main Partmentioning
confidence: 77%
“…The work with mice and health monitoring were conducted in conformity with European FELASA recommendations. For all experiments, mice received water and SBF (V1124-300, ssniff Spezialdi ä ten GmbH) ad libitum or, if indicated ERF (V1574-300, ssniff Spezialitäten GmbH) 3 . Housing facilities were maintained at a temperature of 22.5 ± 0.2 °C, at least 50 % humidity, and a 12:12h light-dark cycle.…”
Section: Methodsmentioning
confidence: 99%